(untitled) (Advancements in Homeopathic Research, 2022)
but where there is no physical disease. For example, chest pain may be caused by stress and no physical disease can be found. A broad range of physical diseases and conditions may be especially prone to being made worse by mental factors. These include skin conditions such as eczema and psoriasis; high blood pressure; heart problems and more. Psychosomatic disorders frequently affect the respiratory and gastrointestinal systems as well as the cardiovascular system.Some physical diseases are thought to be prone to be made worse by mental factors such as stress and anxiety. At any given time, a person’s mental state can affect the degree of severity of a physical disease. Physical symptoms that are caused by mental factors are also called somatization or somatoform disorders. These symptoms are due to increased activity of nervous impulses sent from the brain to various parts of the body. Psychosomatic disorders can have mild to severe effects on one’s quality of life, from interfering with the normal ability to function to causing physical or mental disability.